1987
DOI: 10.1161/01.res.60.5.631
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1-adrenoceptor activity regulates release of adenosine from the ischemic myocardium in dogs.

Abstract: The goal of this study was to test the hypothesis that alpha 1-adrenoceptor activity plays a key role in the release of adenosine from the ischemic myocardium. In 51 open-chest dogs, the left anterior descending coronary artery was perfused through an extracorporeal bypass tube from the carotid artery, and adenosine release into the local coronary vein was measured by the radioimmunoassay technique following the reduction of perfusion pressure for 20 minutes under alpha 1-, alpha 2-, and beta-adrenoceptor atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Indeed, although carvedilol does not have a nitroxy moiety, its chemical structure predicts that the drug could also block ␣ 1 -adrenoceptors, 20 which would cause vasodilation. We cannot exclude this possibility, but the role of ␣ 1 -adrenoceptor blockade in the vasodilatory effect of carvedilol seems likely to be minor, because we have previously reported that blockade of ␣ 1 -adrenoceptors attenuates adenosine release in ischemic myocardium, 21 whereas we found that carvedilol caused an increase of adenosine production. Second, carvedilol may increase vasodilatory substances such as NO or adenosine.…”
Section: Influence Of Carvedilol On Adenosine Release In Ischemic Heartsmentioning
confidence: 71%
“…Indeed, although carvedilol does not have a nitroxy moiety, its chemical structure predicts that the drug could also block ␣ 1 -adrenoceptors, 20 which would cause vasodilation. We cannot exclude this possibility, but the role of ␣ 1 -adrenoceptor blockade in the vasodilatory effect of carvedilol seems likely to be minor, because we have previously reported that blockade of ␣ 1 -adrenoceptors attenuates adenosine release in ischemic myocardium, 21 whereas we found that carvedilol caused an increase of adenosine production. Second, carvedilol may increase vasodilatory substances such as NO or adenosine.…”
Section: Influence Of Carvedilol On Adenosine Release In Ischemic Heartsmentioning
confidence: 71%
“…50 Also, because extracellular adenine nucleotides derived from endothelium, adrenergic nerves, and erythrocytes can be a substrate of ecto-5'-nucleotidase, 51,52 both cytosolic and ecto-5'-nucleotidase may play an important role in adenosine production. We have previously reported that the 1-adrenoceptor antagonist prazosin markedly reduces the release of adenosine from ischemic myocardium either during hypoperfusion 53 or after coronary microembolization 54 (Fig 1); administration of a low dose of prazosin that did not affect basal coronary blood flow reduced coronary blood flow and further exaggerated the ischemic damage, ie, caused an increase in lactate production and a decrease in regional myocardial segment shortening. Because the contribution of -adrenergic activity to the release of adenine nucleotides is also reported in endothelial cells, 55 it is likely that activation of protein kinase C (PKC) by 1-adrenergic stimulation is involved in the production of adenosine in hypoxic hearts.…”
Section: Adenosine Production In the Heartmentioning
confidence: 88%
“…Previous studies from our laboratory demonstrated that myocardial ischemia induced by coronary microvascular obstructions is characterized by the sustained release of adenosine, which causes hyperemic flow in the microcirculation See p 951 surrounding the patchy ischemic lesion. [10][11][12] In these lesions, oxygen-derived free radicals may be continuously generated. Because free radicals may play an important role for an increase in vascular permeability during ischemia13 and cellular swelling during reflow,14 radical scavengers may be effective in attenuating the severity of cellular swelling and, hence, the extent of myocardial necrosis'5 after coronary microvascular obstruction.…”
mentioning
confidence: 99%
“…We have reported that adenosine released from the ischemic myocardium criti-cally determines the contractile and metabolic dysfunction. [10][11][12] Coronary blood flow responses may be improved by free radical scavengers if free radical generation alters adenosine metabolism. Thus, the present study was designed to determine 1) whether coronary microvascular embolization results in myocardial cell swelling, 2) whether free radical scavengers improve myocardial contractile and metabolic dysfunction and prevent myocardial edema (we have examined the effects of free radical scavengers, i.e., superoxide dismutase [SOD, Ube Industries, Tokyo], CV361116 [2-O-octadecylascorbic acid, Takeda Chemical Industries, Osaka, Japan], and the xanthine oxidase inhibitor, allopurinol, on ventricular and coronary dysfunction, lactate production, and myocardial edema after coronary microvascular embolization in dogs), and 3) whether adenosine plays a central role in the beneficial effects of radical scavengers.…”
mentioning
confidence: 99%